Negociaciones de identidad en la radio indígena y étnica colombiana: tres casos de estudio (2014)
The topic of native and ethnic radio, as part of the lack ofresearch on radio in Colombia, has been poorly developed(Cuesta Moreno, 2012a, 2012b). This article shows three studycases: Radio Nasa of Nasa Community, Jujunula Makuira of WayuuCommunity, and Al A With A Wan program of native communityfrom San Andrés island; it also explores the identity perspectivesthat find negotiation spaces in radio production, especially therelationship of their collective identity and the way it affects ordetermines its linguistic use. This research is based on a threestageprocess where producers (practice communities) (Wenger,1998) make a reflection on their function and issue concepts onthe way their identity is reflected from the construction of theirprogramming. Results show that several levels of affiliation toseveral identification facets make it possible to relate, in severalmanners, the communication work of radio and that theseidentifications present in the practice communities have a realimpact on the linguistic radio production of each community.